New facets of larger Nest motifs in proteins. Issue 11 (31st July 2020) - Pal, Debnath; Sahu, Subhankar; Banerjee, Raja
Abstract: The Nest is a concave‐shaped structural motif in proteins formed by consecutive enantiomeric left‐handed (L) and right‐handed (R) helical conformation of the backbone. This important motif subsumes many turn and helix capping structures and binds electron‐rich ligands. Simple Nests are either RL or LR. Larger Nests (>2 residues long) may be RLR, LRL, RLRL, and so forth, being considered as composed of overlapping simple Nests. The larger Nests remain under‐explored despite their widely known contributions to protein function. In our study, we address whether the recurrence of enantiomeric geometry in the larger Nests constrains the peptide backbone such that distinct compositional and conformational preferences are seen compared to simple Nests. Our analysis reveals the critical role of the L helical torsion angle in the formation of larger Nests. This can be observed through the higher propensity of residue or secondary structure combinations in LR and LRL backbone conformation in comparison to RL or RLR, although LR/LRL is considerably lower by occurrence. We also find that the most abundant doublets and triplets in Nests have a propensity for particular secondary structures, suggesting a strong sequence‐structure relationship in the larger Nest. Overall, our analysis corroborates distinct features of simple and the larger Nests. Such insights would be helpful towards in‐vitro design of peptides and peptidomimetic studies. Abstract :